Perceptions of volcanic phenomena: Elements for risk management in Colombia - Hernandez Peña, Yolanda Teresa; Vargas Cuervo, German; Zafra Mejía, Carlos Alfonso (Universidad Pedagógica y Tecnológica de Colombia, 2020)
Cultural risk theory establishes that each society constructs, from its different historical and symbolic references, a differential perception of the risks that may eventually affect them, and in this way a whole symbolic building is generated around the surrounding threats, own vulnerabilities, and the generation of so-called relative security spaces, aspects of importance that relate to possible gaps between prevention and management policies emanating from territorial authorities and local perceptions and reactions of affected communities. Indeed, when analyzing the case of socio-cultural dynamics in areas of influence of volcanic phenomena it is possible to find collective construction processes for the creation of a common perception of the acceptable level of risk. The objective of this article is to demonstrate the different perceptions that exist around volcanic phenomena in Colombia, and their relationship with strategies emanating from official entities focused on risk management. The research was based on an ethnographic approach, complemented by a documentary analysis. It is noted that 80% of the members of indigenous communities interviewed do not establish a gap between nature-culture binarism and relativize the volcanic threat, this type of evidence indicates that the management models and strategies generated from public policy must delve into these cultural constructions to understand how relative security spaces are generated.